Disperata passione e ideologia: fascismo e comunismo nella pubblicistica corsara di Pasolini - Valle, Roberto (Studi Politici, 2023)
Beyond posthumous hagiographies, Pasolini stands beyond the conformist Italian literary horizon of the 19th and 20th centuries unmarked by the sacred charisma of the European curse and cursing. The infernal genealogy of Pasolini’s work derives from Dante’s petrous rhymes centred on dysio as an enormously youthful sensual desire that transcends epochs by displaying the banner of the irredeemable revolutionary force of the curse. Pasolini is not a civil poet but a Byronic privateer for whom desperate passion is the antithesis of ideology, because it is the expression of living life and not of false consciousness. Pasolini does not aspire to be a kind of ‘integrated Rimbaud in a society of imbeciles’.